New triazole-substituted triterpene derivatives exhibiting anti-RSV activity: synthesis, biological evaluation, and molecular modeling - da Silva, Elenilson F.; Antunes Fernandes, Krist Helen; Diedrich, Denise; Gotardi, Jessica; Freire Franco, Marcia Silvana; Tomich de Paula da Silva, Carlos Henrique; Duarte de Souza, Ana Paula; Baggio Gnoatto, Simone Cristina (Beilstein Journal of Organic Chemistry, 2022)
Respiratory syncytial virus (RSV) is a major cause of acute lower respiratory tract infections in infants. Currently, ribavirin, a nucleoside analog containing a 1,2,4-triazole-3-carboxamide moiety, is a first-line drug for its treatment, however, its clinical use has been limited due to its side effects. Here, we designed two new nitroaryl-1,2,3-triazole triterpene derivatives as novel anti-RSV drugs. Their anti-RSV and cytotoxic activity were evaluated in vitro, RSV protein F gene effects by RT-PCR and molecular modeling with inosine monophosphate dehydrogenase (IMPDH) were performed. Compound 8 was the best performing compound, with an EC50 value of 0.053 μM, a TI of 11160.37 and it inhibited hRSV protein F gene expression by approximately 65%. Molecular docking showed a top-ranked solution located in the same region occupied by crystallographic ligands in their complex with IMPDH. The results obtained in this study suggest that compound 8 might be a new anti-RSV candidate.
Keywords: antiviral; betulinic acid; bioisosterism; respiratory syncytial virus; triterpene; ursolic acid